Some of fundamental methodological trends in contemporary developmental psychology - Otto, Kh. (Psichologija, 1983)
The article analyzes and evaluates critically these fundamental methodological trends of different countries in developmental psychology:- Developmental psychology research,- Mental characteristics and performance research,- Age and causal-genetic feature research,- Continuous and cross-sectional research,- Stating-descriptive and experimental-shaping researchThe article concludes by research-strategic conclusions.
Keywords: developmental psychology; development